Study of the Qur'an and Hadith on Social and Community Education - Annisa Naratu Mulya; Alimron; Suharmon (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Qur’an and Hadith teach many social values such as brotherhood, cooperation, kindness, tolerance, generosity, reciprocity, inhumanity and non-reciprocity. Although the Qur’an and the Hadith only provide some examples of social and educational values, they embody them. Islamic social education focuses on teaching good social behavior within a sound psychological framework. These teachings are based on strong Islamic doctrine and a deep sense of faith aimed at promoting participation in society with good morals, mature intellectual balance, and rational behavior. The aim of Islamic education is to inspire, inspire and encourage students to lead a more sustainable life based on good values and morals. Therefore, we expect students’ personalities to contribute more to their attitudes, feelings, and behaviors.